Neutrophil to Lymphocyte Ratio and Mean Platelet Volume as Inflammatory Indicators in Systemic Lupus Erythematosus Nephritis - Ata Bora AYNA; Selime ERMURAT; Belkis Nihan COŞKUN; Halil HARMAN; Yavuz PEHLİVAN (Archives of Rheumatology, 2017)
Objectives: This study aims to evaluate the role of neutrophil to lymphocyte ratio (NLR) and mean platelet volume (MPV) as activation and inflammatory markers in systemic lupus erythematosus (SLE) patients with nephritis. Patients and methods: A total of 108 SLE patients (8 males, 100 females; mean age 35.3±10.2 years; range 16 to 64 years) including 78 patients with renal involvement (8 males, 70 females; mean age 33.9±10.6 years; range 16 to 64 years) (SLEn+ group) and 30 patients without renal involvement (30 females; mean age 39.1±8.2 years; range 22 to 55 years) (SLEn- group) were included in this retrospective study. All patients’ clinical characteristics and laboratory data which include erythrocyte sedimentation rate, C-reactive protein, white blood counts, neutrophil counts, lymphocyte counts, platelet counts, and MPV levels were obtained from medical records. The laboratory data at the highest proteinuria periods of the patients with renal involvement were recorded. Results: Mean MPV (SLEn+ =9.1±2.2, SLEn- =7.9±1.2, p=0.001) and NLR (SLEn+ =5.9±5.9, SLEn- =2.6±2.5, p<0.001) values were significantly higher in lupus nephritis group. Besides, a positive correlation between NLR and C-reactive protein was found in lupus nephritis group (r=1.97, p=0.045). Based on receiver operating characteristic curve with area under the curve of 0.76, cutoff NLR value of 1.93 had 83% sensitivity and 54% specificity [95% confidence interval, 0.66-0.85] in differentiating SLE patients with or without nephritis. Conclusion: Neutrophil to lymphocyte ratio and MPV may be discriminative for lupus nephritis. Also, NLR may be a predictor of lupus nephritis. Both MPV and NLR values may be affected by a great number of factors; therefore, further prospective studies are needed to evaluate the use of these parameters in SLE.